Pembuatan Alat Ukur Distribusi Bunyi dalam Ruang, secara Nirkabel Berbasis Mikrokontroler - Deanu Haratinu Tu’u; Iwan Sugriwan; Arfan Eko Fahrudin (Lambung Mangkurat University Press, 2019)
Sound distribution and background noise, is an important aspect in the making of study-purposed room. Properly distributed sound would ensure everyone in the room to hear the same quality of sound. Good sound quality is defined as a sound that did not diminish its character (sound intensity and sound clarity) significantly to its sound source. In this research, has been fabricated an in-room sound distribution measuring instrument, based on the Arduino microcontroller that equipped with nRF24L01 to be wirelessly functionated. The fabricated measuring instrument consist of 4 transmitter devices and 2 receiver devices. The transmitter devices is an Arduino Pro Mini microcontroller that equipped with nRF24L01 and a sound sensor. The receiver devices is an Arduino Nano microcontroller equipped with nRF24L01, that connected to a PC, and an Arduino Pro Mini microcontroller equipped with nRF24L01 that connected to a speaker. The fabricated measuring instrument equipped with a Python 2.7-based acquisition software to acquire data in real time and store it in CSV (Comma Separated Value) format. Test was carried out to the transmitter devices that equipped with a sound sensor and the receiver device that connected to a speaker. The transmitter devices was compared with a standard sound level meter, and showed 0,65% - 1,24% of error percentage. The test made to receiver device showed that sound intensity of 100 dB could only be achieved with frequency of 2000 Hz and 3000 Hz. On the measurement of sound distribution, the primary data of Einstein Hall sound distribution has been obtained, with 16 sound level measuring point, 7 variations of sound source position, and 5 variations of sound source frequency.The background noise measurement of Einstein Hall of the FMIPA ULM, showed the value varied between 57 dB – 60,56 dB.